2010
DOI: 10.1016/j.alcohol.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure alters the patterns of facial asymmetry

Abstract: Directional asymmetry, the systematic differences between the left and right body sides, is widespread in human populations. Changes in directional asymmetry are associated with various disorders that affect craniofacial development. Because facial dysmorphology is a key criterion for diagnosing fetal alcohol syndrome (FAS), the question arises whether in-utero alcohol exposure alters directional asymmetry in the face. Data on the relative position of 17 morphological landmarks were obtained from facial scans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 43 publications
(67 reference statements)
3
95
1
Order By: Relevance
“…In this context, departures from ideal conditions during ontogeny (i.e., environmental or genetic stress) may reduce the "effi.ciency" of normal developmental processes and increase the levei of FA (Palmer and Strobeck 1 1986;Parsons, 1990;Clarke, 1993;Mf!Jller and Swaddle, 1997) andlor DA (Mclntyre and Mossey, 2002;Hennessy et al, 2004;Schaefer et al 1 2006;DeLeon 1 2007;Ercan et al 1 2008;Klingenberg et al, 2010b;Barrett et al, 2012;Claes et al, 2012). Associations between heterozygosity and FA have been reported in mammals and other species (Soulé, 1979;Biémont, 1983;Leary et al, 1984;Palmer and Strobeck, 1986;Mitton, 1993;Vf!Jllestad, 1999;Leamy et al, 2001), with some exceptions (Wooten and Smith, 1986;Patterson and Paton, 1990;Beacham, American Journal of Physical Anthropology 1991; Britten 1 1996; Gilligan et ai., 2000;Leamy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, departures from ideal conditions during ontogeny (i.e., environmental or genetic stress) may reduce the "effi.ciency" of normal developmental processes and increase the levei of FA (Palmer and Strobeck 1 1986;Parsons, 1990;Clarke, 1993;Mf!Jller and Swaddle, 1997) andlor DA (Mclntyre and Mossey, 2002;Hennessy et al, 2004;Schaefer et al 1 2006;DeLeon 1 2007;Ercan et al 1 2008;Klingenberg et al, 2010b;Barrett et al, 2012;Claes et al, 2012). Associations between heterozygosity and FA have been reported in mammals and other species (Soulé, 1979;Biémont, 1983;Leary et al, 1984;Palmer and Strobeck, 1986;Mitton, 1993;Vf!Jllestad, 1999;Leamy et al, 2001), with some exceptions (Wooten and Smith, 1986;Patterson and Paton, 1990;Beacham, American Journal of Physical Anthropology 1991; Britten 1 1996; Gilligan et ai., 2000;Leamy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DA has been reported in humans (Mcintyre and Mossey, 2002;Schaefer et al, 2006;DeLeon, 2007;Ercan et al, 2008;Klingenberg et al, 2010b), although it is considered a subtle phenomenon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The overall symmetry and dental symmetry have likewise been affected 14 ; to such an extent that a publication on ''fluctuating'' odontometric asymmetry 15 suggested that it may be a marker for FAS, since the mother's alcoholism constitutes a disruptive agent in the odontogenesis at the stage at which the dental organs are still only soft tissue.…”
Section: Synthesismentioning
confidence: 99%
“…Further, we present a simple way to assess both the medial and lateral planes of the face without requiring sophisticated three-dimensional imaging equipment used in current studies 13,19 .…”
Section: Introductionmentioning
confidence: 99%